Weakness in patients with subacromial pain syndrome is local and more pronounced in females. (May 2022) - King, Jacqlyn; Shapiro, Matthew; Karduna, Andrew
Abstract: Background: Subacromial pain syndrome is the predominant cause of shoulder pain, accounting for approximately half of all shoulder complaints. This population presents with weakness of the involved shoulder. However, there is a gap in our understanding of how pain contributes to this weakness, and whether there are sex related differences. Methods: Regional and global isometric strength was tested at the involved shoulder joint and remote joints (uninvolved shoulder and both knees) in patients with subacromial pain syndrome. Data were collected before and after acute pain reduction with a subacromial injection. Findings: Patients demonstrated weakness at the involved shoulder while remote joints demonstrated normal strength. When compared to healthy controls, male patients were shown to exhibit greater levels of weakness than female patients at the involved shoulder, based on comparisons with sex-matched controls using z-scores. Pain reduction (through an anesthetic injection) had no influence on strength in the short-term. Interpretation: Weakness in patients appears to be sex dependent and is not resolved with reduction of pain. This calls into question the assumptions of the physiological causes of this weakness. Highlights: Patients with subacromial pain syndrome demonstrate substantial weakness in their involved shoulder Shoulder weakness in this population is not resolved after pain reduction Female patients exhibit greater levels of weakness than male patients